Hydrogen Sulfide Ameliorated High Choline-Induced Cardiac Dysfunction by Inhibiting cGAS-STING-NLRP3 Inflammasome Pathway. (22nd July 2022) - Bai, Lu; Dai, Jing; Xia, Yuxuan; He, Kaichuan; Xue, Hongmei; Guo, Qi; Tian, Danyang; Xiao, Lin; Zhang, Xiangjian; Teng, Xu; Wu, Yuming; Jin, Sheng
Abstract : Although it is an essential nutrient, high choline intake directly or indirectly via its metabolite is associated with increased risk of cardiovascular disease, the mechanism of which remains to be elucidated. The present study was performed to investigate whether hydrogen sulfide (H2 S) was involved in high choline-induced cardiac dysfunction and explore the potential mechanisms. We found that ejection fraction (EF) and fractional shortening (FS), the indicators of cardiac function measured by echocardiography, were significantly decreased in mice fed a diet containing 1.3% choline for 4 months as compared to the control, while applying 3, 3-dimethyl-1-butanol (DMB) to suppress trimethylamine N-oxide (TMAO, a metabolite of choline) generation ameliorated the cardiac function. Subsequently, we found that feeding choline or TMAO significantly increased the protein levels of cyclic GMP-AMP (cGAMP) synthase (cGAS), stimulator of interferon genes (STING), NOD-like receptor protein 3 (NLRP3), caspase-1, and interleukin-1 β (IL-1 β ) as compared to the control, which indicated the activation of cGAS-STING-NLRP3 inflammasome axis. Moreover, the protein expression of cystathionine γ -lyase (CSE), the main enzyme for H2 S production in the cardiovascular system, was significantly increased after dietary supplementation with choline, but the plasma H2 S levels were significantly decreased. To observe the effect of endogenous H2 S, CSE knockout (KO) mice were used, and we found that the EF, FS, and plasma H2 S levels in WT mice were significantly decreased after dietary supplementation with choline, while there was no difference between CSE KO + control and CSE KO + choline group. To observe the effect of exogenous H2 S, mice were intraperitoneally injected with sodium hydrosulfide (NaHS, a H2 S donor) for 4 months, and we found that NaHS improved the cardiac function and reduced the protein levels of cGAS, STING, NLRP3, caspase-1, and IL-1 β in mice receiving dietary choline. In conclusion, our studies revealed that high choline diet decreased plasma H2 S levels and induced cardiac dysfunction via cGAS-STING-NLRP3 inflammasome axis while H2 S treatment could restore the cardiac function by inhibiting cGAS-STING-NLRP3 inflammasome axis.